A new analogue of Gauss' functional equation - Hiroshi Haruki; Themistocles M. Rassias (International Journal of Mathematics and Mathematical Sciences)
Gauss established a theory on the functional equation (Gauss' functional equation) f(a+b2,ab)=f(a,b)  (a,b>0), where f:R+×R+→R is an unknown function of the above equation.